Political Corrections: The Revolutionary Context and English Retranslations of Johann Georg Zimmermann’s Vom Nationalstolze [On National Pride] (1768) - Tarkka, Laura (TTR, 2021)
This article concerns the English translations of a popular eighteenth-century work on national pride. Originally entitled Von dem Nationalstolze [On National Pride], it was first published in 1758 and then twice revised by the author, Johann Georg Zimmermann (1728-1795). A physician by profession, the Swiss-born Zimmermann treated patriotism as a collective sentiment and soon attracted interest across Europe. Accordingly, the second revised edition Vom Nationalstolze (1768) also appeared in a number of translations, including in English as An Essay on National Pride for the first time in 1771. Since an English retranslation by Samuel Hull Wilcocke was published in 1797 and yet another anonymous retranslation in 1805, the article examines these as attempts to correct the first English translation and to demonstrate the perceived relevance of the source text in the context of the French Revolutionary Wars. Starting from the premise that Zimmermann himself wrote about national pride in order to correct the false preconceptions of his readers, I argue that each translation also participated in the negotiation of a “healthy” form of patriotism. In so doing, the retranslation by Wilcocke in particular took considerable liberties in relation to the source text, while the second retranslator appears to have aspired to produce the most precise and transparent rendition of Zimmermann’s original words. However, as revealed by an examination of the linguistic transformations which the work underwent in Britain, all of the English translations adjusted its political meaning in ways that were significant to contemporary readers.